Correlation Between Cytomegalovirus and Cancer in NHANES Ⅲ - WANG Jiaxin; LI Sen (Zhongliu Fangzhi Yanjiu, 2018)
Objective To investigate the relationship between cytomegalovirus (CMV) seropositivity and the occurrence of cancer using the data from the third National Health and Nutrition Examination Survey (NHANES Ⅲ). Methods The retrospective analysis was performed on the subjects aged 17 or above who participated in NHANES Ⅲ from 1988 to 1994. Results Among 14718 participants, CMV existed in the participants with cancer history, weighted sero-prevalences of CMV in skin cancer and colorectal cancer patients were slightly higher.The percent of female with CMV seropositivity was 10% higher than that of male.Moreover, the possibility of CMV existence in female subjects with breast cancer, cervical cancer and uterine cancer was also slightly higher.Furthermore, CMV prevalence was increased with age (P < 0.01).Unadjusted Logistic regression indicated the presence of CMV was associated with cancer history, skin cancer and breast cancer (P < 0.01).However, such associations were no longer significant after adjusting potential confounders including gender, age, education, race, poverty income ratio, body mass index, smoking status and alcohol-use status. Conclusion The association between CMV seropositivity and cancer occurrence is not significant in general population.